Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and the Yahoo Answers website is now in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
How do I solve the following equations?
The question is
Solve the x:
2(3x + 1) - 3 = 6x -1
If you could write the steps that you take to get the answer that would be great.
Thank you in advance
6 Answers
- Jun AgrudaLv 71 decade agoFavorite Answer
2(3x + 1) - 3 = 6x - 1
6x + 2 = 6x - 1 + 3
0 = 2 - 2
0 = 0
Answer: There is no definite solution to this problem—its number of solutions is infinite. Any value you'll assign to x will work:
Example (x = 0):
2(3[0] + 1) - 3 = 6(0) - 1
2(0 + 1) - 3 = 0 - 1
2(1) - 3 = - 1
2 - 3 = - 1
- 1 = - 1
Example (x = 7):
2(3[7] + 1) - 3 = 6(7) - 1
2(21 + 1) - 3 = 42 - 1
2(22) - 3 = 41
44 - 3 = 41
41 = 41
Example (x = - 7):
2(3[- 7] + 1) - 3 = 6(- 7) - 1
2(- 21 + 1) - 3 = - 42 - 1
2(- 20) - 3 = - 43
- 40 - 3 = - 43
- 43 = - 43
- Anonymous1 decade ago
This is an incorrect Question. It has no answer.
2*3x+2*1-3=6x-1
6x+2-3=6x-1
2-3+1=6x-6x
-1+1=0
0=0
- willy tellLv 41 decade ago
2(3x + 1) - 3 = 6x -1
Multiply out the bracket
6x+2-3=6x-1
6x-1=6x-1
Without a different equation this cannot be solved.
- 1 decade ago
its just pemdas :D
so multiply the 2 into the brackets
2(3x+1) turns into :
6x+2
6x+2-3=6x -1
so it looks like
6x-1= 6x-1
o wow its solved
x= all real numbers enjoy
- Anonymous1 decade ago
step 1: turn computer on, log into yahoo answers
step 2: type the question out and post
step 3: wait until some bored mathematics head sees the question
your welcome, i hope this helped